2018
DOI: 10.1016/j.jshs.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in heart and circulation during physical exercise

Abstract: HighlightsExercise training is beneficial to cardiovascular systemMicroRNAs are responsible for cardiac adaptions to exerciseExercise regulated microRNAs benefits heartMicroRNAs mediate protective effects of exercise in cardiovascular diseasesCirculating microRNAs mediate beneficial effects of exercise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 69 publications
1
63
0
1
Order By: Relevance
“…However, the precise cellular and molecular mechanism for beneficial effects of exercise remains unclear. Nevertheless, non-coding RNAs, and especially microRNAs (miRNAs, miRNAs), constitute a new regulatory component that may play a role in exercise-induced adaptations (Silva et al, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise cellular and molecular mechanism for beneficial effects of exercise remains unclear. Nevertheless, non-coding RNAs, and especially microRNAs (miRNAs, miRNAs), constitute a new regulatory component that may play a role in exercise-induced adaptations (Silva et al, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs, a vital class of upstream regulatory factors of gene expression, negatively regulate gene expression at the post-transcriptional level by binding to the 3 UTR of target mRNAs. miRNAs are broadly involved in various biological processes including development, cell differentiation, and apoptosis in vivo and in vitro (Bartel, 2004;Ouellet et al, 2006;Wang et al, 2018). However, the regulatory miRNA of agrin has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that miRNAs with specific changes in the progression of heart valve disease play key role in the processes of disease progression, such as fibrosis, calcification, matrix degradation remodeling, and inflammation. In addition, some miRNAs could also regulate extracellular body through exosomes and participate in circulation in the exocrine [21][22][23]. Further studies revealed that these miR-NAs can be used as biomarkers for cardiovascular diseases for clinical diagnosis and personalized medicine.…”
Section: Mirnas In Cardiovascular Diseasesmentioning
confidence: 99%